Molecular Dynamics Investigation of Hetero Coalescence between Two Ih Ag55 and Cu55 Clusters at Atomic Scale. Issue 4 (12th February 2023) - Liu, Jinhan; Zhang, Lin
Abstract: Molecular dynamics simulations are performed to explore the coalescence of the two hetero magic Ag55 and Cu55 clusters having icosahedral packing at room temperature, and the structural changes of the alloying Ag–Cu clusters at elevated temperatures. The simulation results reveal the influence of the contacting distances and relative orientations between the two clusters on the coalescing processes as well as the packing patterns of the coalesced binary clusters on heating. The activation energy is used to describe the energy required to initiate the coalescence. The Lode–Nadai parameter's distributions of the coalesced clusters provide more insight into the loading states on the atoms during different stages. The results show that the two clusters appear to form the neck involving twist and "slip" in the initial stage of the coalescence, and the Ag atoms present significant diffusion along the facets of the Cu cluster. As the temperature increases, different packing structures including Icosahedron, core/shell metastable, core@partial‐shell, and half Cu‐half Ag patterns occur. Abstract : In this paper, molecular dynamics simulation is used to reveal the influence of the contacting distance and relative orientations between the Ag55 and Cu55 clusters during the coalescence processes. The influence is reflected in many aspects, including activation energy, Lode–Nadai parameter's distributions, the beginning stages of the coalescence, as well as the packing structure of coalesced clusters.